2019
DOI: 10.1088/1755-1315/278/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of chitosan oligomer prepared using chitosanase of Aeromonas media KLU 11.16

Abstract: Chitosan oligomer is a hydrolysis product of chitosan which can be prepared by enzymatic method, including chitosanase that may be produced by bacteria. Previously, chitosanase from Aeromonas media KLU 11.16 has been purified and characterized. The aim of this study was to analyze the bioactivity of chitosan oligomer prepared by using Aeromonas media KLU 11.16 chitosanase, as antifungal. Chitosan oligomer was prepared from shrimp waste chitosan, and hydrolyzed by 8U chitosanase per gram chitosan. The reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The higher decrease in chitosan viscosity (up to 99.5%) at 16 hours of hydrolysis use a similar enzyme (activity 36.212 U/g) on a larger scale (10-15 times capacity) (Alain Gohi et al, 2016). Hydrolysis of chitosan (DD 74.6%) using pepsin reduced the viscosity by 86% after 1 hours (Yusro Nuri Fawzya et al, 2019). Based on Table 2, the yield of chitosan obtained in this study was 5.17%.…”
Section: Determination Of the Best Treatmentmentioning
confidence: 62%
“…The higher decrease in chitosan viscosity (up to 99.5%) at 16 hours of hydrolysis use a similar enzyme (activity 36.212 U/g) on a larger scale (10-15 times capacity) (Alain Gohi et al, 2016). Hydrolysis of chitosan (DD 74.6%) using pepsin reduced the viscosity by 86% after 1 hours (Yusro Nuri Fawzya et al, 2019). Based on Table 2, the yield of chitosan obtained in this study was 5.17%.…”
Section: Determination Of the Best Treatmentmentioning
confidence: 62%
“…The obtained COS appeared as a yellowish powder with a yield of 68.44%. In previous studies, the COS production yield by the enzymatic method varied-for example, Streptomyces griceus chitosanase was 46.3%; lipase A from Aspegillus niger was 42.5%; Trichoderma viride cellulase was 46.1%; pork pepsin was 52.2% [69]; B. cereus S1 chitosanase was 100% [70]; a combination of chitinase and snailase was 24% [71]; Aeromonas media KLU 11.16 chitosanase was 96.14% [72]; and Bacillus pumilus BN-262 chitosanase was 40% [73]. This indicated that the COS production yield of Paenibacillus sp.…”
Section: Preparation Of Cosmentioning
confidence: 99%
“…The presence of chitin plays a role in helping maintain cell walls, whereas glucans regulate the flexibility and consistency of cell walls (Aranda-Martinez et al 2016). The inhibition growth was suspected by the interaction between chitosan and the plasma membrane which increased the oxidative stress (Fawzya et al 2019). Another research informed that chitosan damage membranes and penetrates into fungal cells, thereby damaging intracellular composition, for instance, inhibit the absorption of nutrients, interfere with mRNA and protein synthesis (El-Guilli et al 2015).…”
Section: Bioactivity Of Chitosan On Stain Fungimentioning
confidence: 99%